(untitled) (Research, Society and Development, 2022)
Objective: To outline the scientific literature on knowledge, attitudes and professional practices in the face of perinatal grief. Methodology: Scope review protocol, prepared according to the Joanna Briggs Institute manual and checklist Prefered Reporing Items for Systematic Review and Meta-Analyses - Extension for Scoping Reviews, registered in the Open Science Framework under no. osf.io/r5gu8. Published and unpublished bibliographic materials will be considered, following the PICO strategy for the elaboration of the guiding question, namely: health personnel (population), knowledge, attitude and practice in health (concept), perinatal death in hospitalized patients (context). A detailed search strategy will be used in the following databases: Virtual Health Library, PubMed and Scopus. The screening will be performed by two independent reviewers, by reading the titles, abstracts and full texts, to extract data from the included material. The included studies will be presented in categories and will receive analytical treatment by theme. Results: They can encourage the stimulation of further research on the subject, contributing to the health practice of professionals.